"It's My Duty to Be Like 'This Is Wrong'": Youth Political Social Media Practices in the Trump Era". Issue 6 (31st October 2019) - Penney, Joel
Abstract: This study used focus groups to explore emergent patterns of youth political social media practices in the Trump era. The participants (U.S. undergraduates aged 18 to 26) suggested that Trump's election was a transformative moment in their lives and that they had shifted their approaches to political social media in response. Many articulated an increased sense of duty and responsibility to use social media to counter perceived problems—such as Trump's ideological extremism and misinformation—online, suggesting the adaption of certain "dutiful citizenship" norms to an "actualizing" mode of political engagement that prioritizes digital self-expression. Simultaneously, Trump's embrace of social media to communicate directly with publics also corresponds with youth "speaking back" as a more exploratory mode of engagement to define political identity. Together, the data highlight the ongoing development of hybrid youth citizenship styles in response to institutional shifts in tactical social media use and growing hyper-partisanship .